Comparison of Performance of Inexpensive Raingages of Different Diameters - Gupta, S. K.; Ullah, Wasi; Babu, Ram; Nayal, M. S. (Indian Forester, 1971)
Results of study conducted to find suitable raingages have shown that the cylinder having diameter of 7.5 to 12.5 cm record comparable data with standard raingage when installed at any height varying from 30 to 90 cm. The use of diameter less than 7.5 cm is not desirable as they record considerable high rainfall.For use of extension departmepts and also where research requires large scale use of raingages, the inexpensive raingages can be constructed by using ordinary G.I. sheet Cylinder or G.I. pipe of diameter between 7.5 to 12.5 cm The depth of rainfall can be directly measured by observing the water accumulated depth in the cylinder. The cost involved in these types of raingages may vary (depending on the material used) from Rs. 5/- to Rs. 20/- per raingage.